Effectiveness of a Family Unit Empowerment Model in Improving Diabetes Management, Family Empowerment, and Family Support among Adults with Type 2 Diabetes Mellitus: A Quasi-Experimental Study - Trisnadewi, Ni Wayan; Adiputra, I Made Sudarma; Oktaviani, Ni Putu Wiwik (Journal of Applied Nursing and Health, 2026)
Background: Diabetes mellitus (DM) remains a major public health challenge in Indonesia, with its prevalence continuing to increase. Although incurable, effective long-term management can maintain patients' quality of life. Family involvement is essential in supporting adherence to diabetes management, yet evidence on structured family-unit empowerment interventions, particularly in community settings, remains limited. Therefore, this study aimed to evaluate the effectiveness of the Family Unit Empowerment Model in improving diabetes management, family empowerment, and family support among patients with type 2 diabetes mellitus (T2DM). Methods: This study employed a quasi-experimental one-group pre-test–post-test design and followed the TREND (Transparent Reporting of Evaluations with Nonrandomized Designs) reporting guideline. A total of 140 patients with T2DM registered at the Blahbatuh 2 Gianyar Community Health Center were recruited through purposive sampling between December 2022 and July 2023. Inclusion criteria included a confirmed T2DM diagnosis, residence with family, ability to communicate effectively, and provision of informed consent. The independent variable was the Family Unit Empowerment Model; dependent variables were diabetes management, family empowerment, and family support, measured using the Summary of Diabetes Self-Care Activities (SDSCA), the Family Empowerment Scale (FES), and the Diabetes Family Support Scale, respectively (all Cronbach’s α ≥ 0.70). The intervention consisted of four structured weekly family-based health education sessions delivered over one month. Data were analyzed using the Wilcoxon Signed-Rank Test, with a significance level of p < 0.05. Results: Statistically significant improvements in median scores were observed for all three outcome variables following the intervention. The proportion of families in the good empowerment category increased from 37.1% to 55.7% (p < 0.001, r = 0.54). For family support, the proportion reporting high support increased from 44.3% to 49.3%, with a significant rise in median scores (p < 0.001, r = 0.49). Diabetes management improved, with poor-category cases decreasing from 40.7% to 27.9% (p < 0.001, r = 0.33). Conclusion: Participation in the Family Unit Empowerment Model was associated with statistically significant improvements in diabetes self-management behaviors, family empowerment, and family support among patients with T2DM. Because the single-group design and reliance on self-reported outcomes preclude causal attribution, these findings should be interpreted as preliminary. They provide promising support for family-centered empowerment approaches in community-based diabetes care and a rationale for evaluation in adequately powered, controlled, multicenter trials that incorporate objective clinical outcomes before broad implementation is recommended.